БЮРОКРАТЫН ОНОЛЫН АСУУДАЛ БА СУДЛАГДСАН БАЙДАЛ - Ц.Батболд (Politology, 2023)
In this articles main context shows researchers treatments how to study of historical time, and have been made the conclusion for implementing arrangement of administration of government’s main mechanism. This article is to make defining approaches of evaluations its character, historical time, methodology treatments of empiric study, theoretical, express researchers attitude.